Losing heart : the moral and spiritual miseducation of America's children - Shapiro, H. Svi (L. Erlbaum Associates, 2006)
Explores the ideological and attitudinal functions of schools, looking especially at what is called the 'hidden curriculum.' This book offers both an analysis of the role of education in producing and maintaining attitudes and values, and self-oriented culture and a different vision for what our schools should be about.